2019
DOI: 10.1111/jfb.14210
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of Phoxinus from the upper Krka River (Adriatic Basin) in Croatia (Actinopterygii: Leuciscidae), first discovered as a molecular clade

Abstract: Using morphometric, meristic and qualitative characters, we confirmed a specific status of a clade discovered based on molecular data only. The newly described species Phoxinus krkae has a very local distribution in the upper Krka River but is easily morphologically distinguished from geographically neighbouring species with much wider ranges: Phoxinus lumaireul, Phoxinus marsilii and Phoxinus csikii. Phoxinus krkae is well differentiated in statistical analyses and differs from other species of Phoxinus in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 8 publications
3
29
0
Order By: Relevance
“…Numbers in the y-axis show the coefficient of assignment F I G U R E 4 Principal component analysis (PCA) of microsatellite genotype data for five populations representing three species as follows: population A: Phoxinus krkae; population B: Phoxinus marsilii; population C: Phoxinus marsilii; population D: Phoxinus lumaireul s. l.; population E: Phoxinus lumaireul s. l. Dots represent individuals to be the result of evolutionary history of the area (Palandači c et al, 2020). Because the existing markers cannot clearly resolve this issue, new microsatellite markers developed in this study can be utilized in the detection of hybridization events and migration patterns of Phoxinus species in this area.Microsatellite data are in accordance with existing data on these populations and species, where P. krkae was first detected as separate molecular lineage based on the mtDNA and later on described as a new species, distinct from the surrounding P. lumaireul populations(Bogutskaya et al, 2019;Vuci c et al, 2018). For P. marsilii, results also show a partial genetic divergence of the two populations analysed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Numbers in the y-axis show the coefficient of assignment F I G U R E 4 Principal component analysis (PCA) of microsatellite genotype data for five populations representing three species as follows: population A: Phoxinus krkae; population B: Phoxinus marsilii; population C: Phoxinus marsilii; population D: Phoxinus lumaireul s. l.; population E: Phoxinus lumaireul s. l. Dots represent individuals to be the result of evolutionary history of the area (Palandači c et al, 2020). Because the existing markers cannot clearly resolve this issue, new microsatellite markers developed in this study can be utilized in the detection of hybridization events and migration patterns of Phoxinus species in this area.Microsatellite data are in accordance with existing data on these populations and species, where P. krkae was first detected as separate molecular lineage based on the mtDNA and later on described as a new species, distinct from the surrounding P. lumaireul populations(Bogutskaya et al, 2019;Vuci c et al, 2018). For P. marsilii, results also show a partial genetic divergence of the two populations analysed.…”
supporting
confidence: 88%
“…Microsatellite data are in accordance with existing data on these populations and species, where P. krkae was first detected as separate molecular lineage based on the mtDNA and later on described as a new species, distinct from the surrounding P. lumaireul populations (Bogutskaya et al ., 2019; Vucić et al ., 2018). For P. marsilii , results also show a partial genetic divergence of the two populations analysed.…”
Section: Discussionmentioning
confidence: 99%
“…While Leuciscinae in Europe are well represented (>320 species), the closest relatives of Phoxinus are distributed in the Pacific basin [54,106,107]. Morphologically, Phoxinus is, in general, characterized by a low level of phenotypic diversity, in contrast to its high level of genetic diversity [38,98,108], whereas Leuciscinae (including Delminichthys, Phoxinellus and Telestes) are highly phenotypically divergent and taxonomically structured in a complex system that also corresponds to their genetic patterns. Nevertheless, when comparing the distribution ranges with other unrelated taxa spread in the Dinaric Karst, some common patterns emerge.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, the European Phoxinus Rafinesque, 1820 have been intensively researched and studies revealed high levels of molecular and morphological diversity, and a complex taxonomy (Palandačić et al 2015(Palandačić et al , 2017(Palandačić et al , 2020Vucić et al 2018;Bogutskaya et al 2019;Corral-Lou et al 2019;De Santis et al 2020). Some genetically and morphologically diagnosable clades were given the rank of species, either new (Bogutskaya et al 2019;Denys et al 2020) or re-validated (Bogutskaya & Naseka 2004;Palandačić et al 2017;Bogutskaya et al 2019), e.g., P. marsilii Heckel, 1836 and P. colchicus Berg, 1910. However, a number of clades requiring integrated research to help clarify their phylogeny and taxonomic identities, remained.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Furthermore, some nomenclatural issues such as the applicability of older available names, have become of paramount importance in this field. While studies on these issues have mainly analysed the material of Phoxinus from the western part of its range (Kottelat 2007;Palandačić et al 2015Palandačić et al , 2017Palandačić et al , 2020Vucić et al 2018;Bogutskaya et al 2019;Corral-Lou et al 2019;De Santis et al 2020;Denys et al 2020), the areas to the east and north-east of the Danube Basin have been less thoroughly studied.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%